Influence of polyvinylpyrrolidone (PVP) capping layer on silver nanowire networks: theoretical and experimental studies. Issue 37 (29th March 2016) - Hwang, Jinyoung; Shim, Youngseon; Yoon, Seon-Mi; Lee, Sang Hyun; Park, Sung-Hoon
Abstract : By adjusting the polyvinylpyrrolidone (PVP) capping layer thickness on silver nanowire networks, improved electrical and optical properties were obtained, which was confirmed both experimentally and theoretically (Molecular dynamics and Monte Carlo simulations). Abstract : This study conducts an experimental and theoretical investigation of the influence of a polyvinylpyrrolidone (PVP) capping layer on silver nanowire (AgNWs) networks. Through a washing method, a PVP layer on AgNWs was removed and the contact resistance ( R C ) between AgNWs was reduced, thereby obtaining a reduced sheet resistance ( R S ) of AgNW film. During the washing process, the thickness of the PVP layer decreased to 1 nm with an increasing number of washes, as demonstrated by a molecular dynamics simulation. In addition, the size of the change in R S resulting from the reduction in R C by the removal of PVP decreased as the areal coverage of NWs increased. In order to explain the results, Monte Carlo simulations were performed and the results show that the reduction in R C by the removal of PVP apparently reduces the value of R S more as the areal coverage of NWs decreases and the initial value of R C of the network increases. Saturation of the reduction in R S also occurs when the inherent resistance of AgNW ( R NW ) becomes dominant. Along with the electrical properties, improved transmittance and a reduction in haze were observed with the removal of PVP, and the results prove that R S can be reduced by reducing R C without impairing the optical properties of transparent conducting electrodes.